BASICS OF ORGANIZING THE PROCESS OF PHYSICAL TRAINING OF INTERNAL AFFAIRS OFFICERS (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the specific aspects of organizing the physical training process of cadets of the Academy of Internal Affairs. Physical training is an independent section of service and combat training and is one of the most important components in the formation of professional skills of employees of internal affairs bodies. It involves the formation of professionally important physical qualities and movement skills applicable to service, including combat combat techniques and methods of overcoming various natural and artificial obstacles. The article analyzes the physical qualities necessary for cadets of the Academy of Internal Affairs and the features of their formation, as well as indicates the problems and solutions that make the training process more effective. A high level of physical training significantly affects indicators such as the effectiveness of apprehending criminals, the coordination of the activities of service and combat groups, the maximum use of the combat capabilities of weapons and equipment, the effectiveness of firing from combat weapons, tolerance to adverse factors of service and combat activities, and the reduction of losses and other damaging factors during special operations.
Keywords: Physical training, Physical fitness, Internal affairs officers, Law enforcement personnel, Professional readiness, Endurance development, Strength training, Speed and agility, Service-oriented physical training